Multiple High Grade Rhabdoid Papillary Meningiomas Mimicking Choroid Plexus Carcinoma: A Case Report - Arezoo Eftekhar-Javadi; Dorna Motevalli; Ahmad Pourrashidi Boshrabadi; Hedieh Moradi Tabriz; Hoda Asefi (Iranian Society of Pathology, 2019)
Rhabdoid papillary meningioma is an uncommon aggressive variant of meningioma which has the potential to metastasize and spread throughout the brain and even out of the cranium. Herein, we present recurrence of the brain tumor in a 26-year-old woman. The patient had history of the surgery for two lesions in the right temporal lobe and the left cerebellopontine angle. Imaging showed three lesions in the right temporal lobe, the right occipital horn wall, and the left cerebellopontine angle. These radiologic findings were mostly suggestive of atypical meningioma. In the surgical view, the mass was solid-cystic reddish Cauliflower-shaped in the right temporal lobe attaching to the temporal horn. The microscopic examination showed a cellular neoplasm with the sheet-like and papillary growth pattern. Individual cells had vesicular nuclei some with prominent nucleoli and eosinophilic cytoplasm. The areas of the tumor cells showed round eccentric nuclei and prominent nucleoli with eosinophilic cytoplasm. Immunohistochemistry studies showed diffuse positivity of tumor cells with Vimentin, EMA, and S100. The overall clinical, radiological and histopathological examinations were compatible with high grade rhabdoid-papillary meningiomas. In the present case study, we discuss imaging and histomorphological features of this rare entity of meningiomas.